2021
DOI: 10.1519/jsc.0000000000003075
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Deficit During Jumping Tasks: Relationship With Speed and Change of Direction Speed Performance

Abstract: Research to date has investigated the phenomenon of the bilateral deficit (BLD); however, limited research exists on its association with measures of athletic performance. The purpose of the present study was to investigate the magnitude of the BLD and examine its relationship with linear speed and change of direction speed (CODS) performance. Eighteen physically active and healthy university students performed double and single leg countermovement jumps (CMJ), drop jumps (DJ) and standing broad jumps (SBJ), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
3
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 36 publications
(61 reference statements)
8
34
3
5
Order By: Relevance
“…COD test showed a lower magnitude of asymmetry (COD5: 4.60% ± 2.51% and COD10: 3.02% ± 1.74%) in comparison to the jump and iso-inertial power tests, which is in agreement with previous research (Fort-Vanmeerhaeghe et al, 2015;Dos'Santos et al, 2018;Madruga-Parera et al, 2019). The COD tests' inability to detect asymmetries could be due to two reasons: first, there is a strong linear speed component during COD, mainly in COD10 (Madruga-Parera et al, 2019), and second, sprint times are far more replicable than power outputs during jump (Bishop et al, 2019a) or iso-inertial tests.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…COD test showed a lower magnitude of asymmetry (COD5: 4.60% ± 2.51% and COD10: 3.02% ± 1.74%) in comparison to the jump and iso-inertial power tests, which is in agreement with previous research (Fort-Vanmeerhaeghe et al, 2015;Dos'Santos et al, 2018;Madruga-Parera et al, 2019). The COD tests' inability to detect asymmetries could be due to two reasons: first, there is a strong linear speed component during COD, mainly in COD10 (Madruga-Parera et al, 2019), and second, sprint times are far more replicable than power outputs during jump (Bishop et al, 2019a) or iso-inertial tests.…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest the data being presented in this article can be interpreted with confidence for further analysis (Turner et al, 2015). Previous research supports that the level of experience and the structured strength and conditioning training (inclusive of speed and jump training) performed during the season seem to contribute to the good reliability of the data (Bishop et al, 2019a). Regarding the asymmetry scores observed in the present study, iso-inertial power tests showed the largest asymmetries in both mean and peak power (21.27% ± 15.55% and 21.68% ± 18.85%, respectively) across the different proposed tests, whereas the FIGURE 5 | Individual asymmetry data for iso-inertial power test.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations